PENGARUH BAURAN PEMASARAN (MARKETING MIX) TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK KARA SANTAN PT ENSEVAL PUTERA MEGATRADING, Tbk - Sylvia Shareen; Nur Rahmah Andayani (Politeknik Negeri Batam, 2018)
This study aims to determine and analyze the influence of marketing mix which consists of product variables, prices, promotions, places, people, and the process of purchasing decisions on products Kara Santan PT. Enseval Putera Megatrading, Tbk simultaneously or partially. Population in this research is customer of PT. Enseval Megatrading Putera Tbk Batam Branch who had a history of purchases Kara Santan period in 2016. The analysis method used in this research is descriptive analysis and multiple regression analysis using SPSS 20. Hypothesis testing using T test and F test value of α = 5%. The results showed that in partial product, price, promotion, people, and processes of positive and significant influence on purchasing decisions, althought place have no effect and significant impact on purchasing decisions, and simultaneously all the variable positive and significant impact on purchasing decisions PT. Enseval Putera Megatrading, Tbk.